Analysis of Students' Perception of Small Group Discussion Techniques in Expository Text Writing Activities at SMAN 17 Pekanbaru - Imeldah Imeldah; Qona’ah Nuryan Arif; Ardiya Ardiya (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to analyze students’ perceptions of the implementation of small group discussion techniques in expository text writing activities. The research employed a qualitative descriptive design and was conducted at SMAN 17 Pekanbaru on 29 August 2025. The population consisted of 200 eleventh-grade students, and 20 students were selected purposively as the sample. Data were collected through classroom observation, face-to-face interviews, and documentation of students’ expository texts. Thematic analysis (Braun & Clarke, 2006) was applied to analyze the data. The findings reveal that students generally perceive small group discussion positively. The technique helped students generate ideas, enrich vocabulary, improve text organization and cohesion, and build confidence in writing. However, several challenges were identified, including unequal participation, occasional code-switching to Bahasa Indonesia, and limited time allocation. Documentation of students’ texts confirmed improvements in structure, coherence, and lexical variety after participating in group discussions. The study concludes that small group discussion is an effective strategy to support students’ expository writing, with recommendations for structured group roles, better time management, and active teacher facilitation.